The Issue of the Living Wage in the Context of Poverty in the Conditions of the Slovak Republic as Democratic State - Lenka Lachytova; Ivana Lehotay Pandova (Vasyl Stefanyk Precarpathian National University, 2024)
Pervasive poverty is an important global problem that seriously affects the quality of life of individuals and families. According to the UN Sustainable Development Goals, the fight against poverty is one of the key tasks for ensuring social justice and economic development. Each country has a responsibility to ensure the well-being of its citizens, including protection from social and material deprivation.In the Slovak Republic, there is an increase in poverty, which is due to the influence of various negative factors and events that affect the social structure of society. This article is devoted to the analysis of the subsistence minimum as a key tool of social assistance in the conditions of changes that have taken place in recent years, with a special emphasis on the election periods of 2016-2020 and 2020-2023. It examines the importance of a living wage in the context of the fight against poverty, which is necessary to ensure basic human rights. The article also defines the factors that should be given special attention in order to improve the subsistence minimum system. Particular emphasis is placed on clarifying the essence and objectives of the last major amendment in the field of living wage, which entered into force in April 2023 in the Slovak Republic. Some political changes in certain election periods are also discussed from the point of view of their influence on the development of the state social assistance system, which includes the institution of the living wage. This article aims to deepen the understanding of the complex interrelationships between poverty, social policy and economic development, with the aim of improving the lives of the citizens of the Slovak Republic and achieving the Sustainable Development Goals in the field of poverty reduction. This work reflects the importance of strengthening social security and ensuring inclusive economic growth, which is critical for the sustainable development of society.